THE LINGUISTIC FEATURES OF INDONESIAN CHILDREN POETRY - Mulyono, Tri (Sanata Dharma University, 2018)
This study was inspired by the fact that the study in the field of children literature is rarely found in today's era, especially the study of poetry. Even though there are a lot of children poetries written by child poets nowadays, but still the research in children poetry is still low. Therefore, the researchers conducted this study with hope to enrich study in the field of children literature. Specifically, this study limited its objective into describing the language features of Indonesian children poetry. To pursue such objective, this study employed 50 titles of Indonesian children poetry written by child poets. The data of those poetries were collected by reading and writing (recording). Once the data were collected, they were analyzed in descriptive qualitative. The results show that the linguistic features of Indonesian children poetry written by child poets is realized on word shortening, meaning deviation, the use of foreign language words and Javanese language.DOI:https://doi.org/10.24071/ijhs.2018.010208